Indonesia Penyakit Degeneratif Pada Lansia: Pencegahan Dan Penanganannya: Degenerative Diseases in the Elderly: Prevention and Treatment - Sonia Fijri; Suwandi; Eva Gustia; Oktaria Trisna Dewi; Lena Marianti (CONS-IEDU: Jurnal Program Studi Bimbingan Dan Konseling Islam, 2022)
Degenerative diseases are a group of diseases characterized by a decrease in organ or tissue function due to the aging process. The elderly are a group that is vulnerable to these diseases, including osteoporosis, arthritis, heart disease, dementia, and type 2 diabetes mellitus. Risk factors such as aging, unhealthy lifestyles, genetics, and environmental exposure play a role in increasing the prevalence of degenerative diseases in the population elderly. This article discusses the importance of prevention through a healthy lifestyle, such as regular physical activity, a balanced diet, and regular health checks. Apart from that, treatment that includes medical treatment, physical therapy and psychosocial support is an essential step in improving the quality of life of the elderly. Family and community support also plays a role in reducing the psychological and financial impact of degenerative diseases. Through understanding and implementing effective prevention and treatment strategies, it is hoped that the incidence and complications of degenerative diseases can be minimized, so that the elderly can enjoy a healthier and more productive life.